Validation of quality indicators in TYKS Urology - Lautiainen, Niilo (My University, 2026)
Monitoring the quality of healthcare requires reliable indicators that accurately reflect clinical performance. Turku University Hospital (TYKS) is planning to implement automated quality indicators (MILA indicators) to monitor the quality of urological cancer care. These indicators measure time intervals related to diagnosis, treatment, and patient information. The indicators focus on prostate, kidney, and bladder cancers. The aim of this study was to validate these indicators and modify them to be more appropriate before implementation. The study cohort consisted of patients treated at TYKS Urology between years 2018 and 2024. Six MILA indicators were evaluated. Automated algorithms retrieved relevant diagnostic and procedural events from electronic patient records to calculate waiting times. Validation was performed by manually reviewing predefined patient samples. Validation revealed several sources of error across the indicators. Some errors were present in all indicators, and some were specific to certain event selection. Several modifications were proposed to improve the algorithms, including revised inclusion criteria, additional diagnostic or procedural codes, and adjusted time thresholds. Not all modifications could be fully validated within the timeframe of this study. Further refinement of the algorithms is required to optimize event selection and time interval calculation. In conclusion, automated quality indicators require careful validation before clinical implementation. With further refinement, the MILA indicators will provide a useful tool for monitoring treatment delays, improving resource allocation, and enabling comparison of time delays against other countries and healthcare regions.
Keywords: quality indicators; urological cancers; surgery waiting time